Excess Volatility in European Equity Style Indices - New Evidence - Marian Berneburg (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2006)
Are financial markets efficient? One proposition that seems to contradict this is Shiller's finding of excess volatility in asset prices and its resulting rejection of the discounted cash flow model. This paper replicates Shiller's approach for a different data set and extends his analysis by testing for a long-run relationship by means of a cointegration analysis. Contrary to previous studies, monthly data for an integrated European stock market is being used, with special attention to equity style investment strategies. On the basis of this analysis' results, Shiller's findings seem questionable. While a long-run relationship between prices and dividends can be observed for all equity styles, a certain degree, but to a much smaller extent than in Shiller's approach, of excess volatility cannot be rejected. But it seems that a further relaxation of Shiller's assumptions would completely eliminate the finding of an overly strong reaction of prices to changes in dividends. Two interesting side results are, that all three investment styles seem to have equal performance when adjusting for risk, which by itself is an indication for efficiency and that market participants seem to use current dividend payments from one company as an indication for future dividend payments by other firms. Overall the results of this paper lead to the conclusion that efficiency cannot be rejected for an integrated European equity market. – – Sind die Finanzmärkte effizient? Das Ergebnis von Shillers (1981) berühmter Untersuchung über "Excess Volatility" in Aktienpreisen verneinte diese Frage. Demnach wären Vermögenspreise nicht als diskontierte Summe aller zukünftigen Einkommensströme (Present Value) darstellbar. Dieser Aufsatz wendet Shillers Ansatz auf einen anderen Datensatz an und erweitert ihn um einen Test auf eine langfristige Beziehung zwischen Preisen und Dividenden (cointegration test). Es werden monatliche Daten von drei verschiedenen Investmentstrategien für einen europäischen Gesamtmarkt verwendet. Die Resultate bestätigen Shillers Ergebnisse nur bedingt. Während mit dem Koointegrationstest für alle drei Investmentstrategien eine langfristige Beziehung zwischen Preisen und Dividenden gefunden werden kann, lässt sich "Excess Volatility", wenn auch in deutlich geringerem Umfang als es Shiller ausweißt, nicht ablehnen. Eine weitere Lockerung von Shillers Annahmen dürfte die übermäßige Reaktion der Preise auf Veränderungen in Dividendenzahlungen komplett eliminieren. Zwei interessante Randergebnisse sind, dass alle drei Investmentstrategien auf risikoadjustierter Basis die gleiche Performance aufweisen, und dass Marktteilnehmer offensichtlich aktuelle Dividendenzahlungen eines Unternehmens als Prädiktor für zukünftige Zahlungen anderer Unternehmen heranziehen. Alles in allem lässt sich auf Basis dieser Ergebnisse sagen, dass Effizienz in einem europäischen Gesamtaktienmarkt nicht abgelehnt werden kann.
urn:nbn:de:gbv:3:2-5520
Keywords: G12; G14; 330; Aktienmarkteffizienz; Discouned Cashflow; Excess Volatility; Variance Bound Tests; Kointegration; Equity Market Efficiency; Discounted Cashflow; Excess Volatility; Variance Bound Test; Cointegration Tests